Analysis of Factors Affecting Employee Performance at the Health Office - Eva Suzanna; Lilis Suryani; Chairil Zaman; Hamyatri Rawallah; Musa Saho (School of Health Sciences Al-Ma'arif, 2025)
Employee performance is a measure that can be used to establish a comparison of the results of the implementation of tasks, responsibilities given by the organization to measure work performance or organizational performance. Currently, there is still no fulfillment of health worker standards in accordance with the Ministry of Health's moratorium at the Empat Lawang District Health Office. This study aims to determine the overview of employee performance analysis at the Health Office of Empat Lawang Regency in 2024. The design of this study is a quantitative analytical survey with cross sectional approach. The population of this study was all employees of the Health Office of Empat Lawang Regency in 2024, which amounted to 95 respondents. Sampling in this study using total sampling technique, so that the sample in this study amounted to 95 respondents. Data collection using questionnaires. Bivariate data analysis using Chi-Square test and multivariate multiple logistic regression. The results showed that there was a relationship between age (p value 0.042), education (p value 0.013), officer working time (p value 0.000), workload component (p value 0.002), workload standard (p value 0.011), and supporting task standard (p value 0.000), to the performance of employees in the Health Office of Empat Lawang Regency in 2024. The most dominant factor with employee performance is the workload component (p value 0.002), (OR 4.053). For the Health Office should be able to improve employee performance by setting the types of tasks and job descriptions that are actually carried out by certain types of SDMK in accordance with the basic duties and functions of employees.